Numerical Simulation of Chemical and Nuclear Contamination Transport in Aquifers and its Possible Application for the Control of Environmental Impacts due to Mining Activity (The Australasian Institute of Mining and Metallurgy, 1988)
The paper describes a simulating method.for ground water contamination originating from industrial and mining activrty. The finite difference model simulates heat, mass and solute transport. The applied stochastical method for dispersion provides more accurate solution of mass transport modelling. This method gives a more realistic approach of chemical processes in an aquifer depending on temperature.